2017
DOI: 10.1096/fj.201601059rr
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic memory in response to environmental stressors

Abstract: eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 70 publications
(102 reference statements)
3
44
0
2
Order By: Relevance
“…Environmental adaptations require fine-tuning of gene transcription supervised by chromatin modifications. A repertoire of epigenetic regulators controls the milieu of the epigenetic marks that influence chromatin compaction or opening (Vineis et al, 2017). Among transcriptional repressors, class IIa HDACs are important regulators of genetic programmes, which orchestrate different cellular fates.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental adaptations require fine-tuning of gene transcription supervised by chromatin modifications. A repertoire of epigenetic regulators controls the milieu of the epigenetic marks that influence chromatin compaction or opening (Vineis et al, 2017). Among transcriptional repressors, class IIa HDACs are important regulators of genetic programmes, which orchestrate different cellular fates.…”
Section: Introductionmentioning
confidence: 99%
“…As these children aged, they developed a spectrum of disorders that had no obvious genetic history within their respective families. Later, alterations in the DNA methylation patterns were identified in these individuals that suggested that these disorders might be linked to the differential epigenetic modifications that were potentially written during this period of famine . Comparable findings have been observed for other populations in similar contexts around the world …”
Section: Introductionmentioning
confidence: 62%
“…Later, alterations in the DNA methylation patterns were identified in these individuals that suggested that these disorders might be linked to the differential epigenetic modifications that were potentially written during this period of famine. [1][2][3]6] Comparable findings have been observed for other populations in similar contexts around the world. [7] In a recent study, we examined how the AMP activated protein kinase (AMPK), which has been well described for its role in maintaining energy homeostasis in response to several stresses, [8,9] is also involved in blocking specific chromatin modifications and epigenetic changes in Caenorhabditis elegans larvae that are subjected to starvation.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations